A State-of-Charge-Based Flexible Synthetic Inertial Control Strategy of Battery Energy Storage Systems - You, Feng; Si, Xiuli; Dong, Rong; Lin, Dong; Xu, Yien; Xu, Yiming (Frontiers in Energy Research, 2022)
The power system would face the issues of the system frequency stability when high scales of variable renewable energy generation are integrated in electric power systems. Battery energy storage systems (BESSs) with advanced control capability and rapid control response become a countermeasure to solve the issues of the system frequency stability. This research addresses a flexible synthetic inertial control strategy of the BESS to enhance the dynamic system frequency indices including the frequency nadir, settling frequency, and rate of change of the system frequency. To this end, the control loops based on the frequency excursion and rate of change of the system frequency are implemented into the d-axis controller of the BESS. The adaptive control coefficient of both control loops could be adjusted according to the instantaneous state of charge (SOC) so that it can inject more power to grid at a higher SOC. The benefits of the proposed combined inertial control strategy are investigated with various sizes of the disturbance and SOCs of the BESSs. Results successfully illustrate that the proposed combined inertial control strategy of the BESS is capable of enhancing the system frequency stability so as to promote the variable renewable energy accommodation.